Reimagining Religion in the Contemporary World: Adaptation, Plurality, and Interdisciplinary Engagement - Busro, Busro (UIN Sunan Gunung Djati Bandung, 2024)
This editorial introduces Volume 8, Issue 2 (August 2024) of Religious: Jurnal Studi Agama dan Lintas Budaya, featuring six original research articles by 17 authors from 12 institutions across seven countries. Together, these contributions offer critical insights into the evolving role of religion in an era marked by digital transformation, pluralistic tensions, and institutional shifts. The issue explores key themes such as interfaith relations, digital ethics, pilgrimage tourism, gender justice, and religious resilience amid global crises. The editorial reflects on the adaptability of religion as a living tradition, highlighting its ability to respond to challenges like secularisation, misinformation, and mental health. It also discusses the reimagination of the sacred across digital, legal, educational, and touristic domains. Furthermore, it emphasises the urgency of interdisciplinary religious studies, demonstrating how engagement with fields such as psychology, media studies, political science, gender theory, and law enriches both scholarship and practice. This editorial calls for a sustained, collaborative, and responsive approach to the study of religion in today’s interconnected world.